Genome transplantation in bacteria: changing one species to another - Lartigue, Carole; Glass, John I; Alperovich, Nina; Pieper, Rembert; Parmar, Prashanth P; Hutchison, 3rd, Clyde A; Smith, Hamilton O; Venter, J Craig (Science (American Association for the Advancement of Science), 2007)
As a step toward propagation of synthetic genomes, we completely replaced the genome of a bacterial cell with one from another species by transplanting a whole genome as naked DNA. Intact genomic DNA from Mycoplasma mycoides large colony (LC), virtually free of protein, was transplanted into Mycoplasma capricolum cells by polyethylene glycol-mediated transformation. Cells selected for tetracycline resistance, carried by the M. mycoides LC chromosome, contain the complete donor genome and are free of detectable recipient genomic sequences. These cells that result from genome transplantation are phenotypically identical to the M. mycoides LC donor strain as judged by several criteria.